2011
DOI: 10.1074/jbc.m111.239244
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Biosynthesis of Human Endothelin B Receptor by the Cyclodepsipeptide Cotransin

Abstract: The specific inhibition of the biosynthesis of target proteins is a relatively novel strategy in pharmacology and is based mainly on antisense approaches (e.g. antisense oligonucleotides or RNA interference). Recently, a novel class of substances was described acting at a later step of protein biosynthesis. The cyclic heptadepsipeptides CAM741 and cotransin were shown to inhibit selectively the biosynthesis of a small subset of secretory proteins by preventing stable insertion of the nascent chains into the Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Apratoxin A, a cyanobacterial metabolite, has been shown to inhibit cotranslational translocation in vitro (Liu et al, 2009), but the blocked step is unknown. Furthermore a group of closely related cyclic heptadepsipeptide inhibitors including HUN-7293, CAM741 (Besemer et al, 2005) and a simplified version thereof called cotransin (Garrison et al, 2005) have been found to inhibit cotranslational translocation of VCAM1 and other specific substrates (Maifeld et al, 2011;Westendorf et al, 2011). Photoaffinity labeling has identified Sec61a as the target (MacKinnon et al, 2007), which was confirmed by isolation of resistance mutations in SEC61A1 (MacKinnon et al, 2014).…”
Section: Introductionmentioning
confidence: 83%
“…Apratoxin A, a cyanobacterial metabolite, has been shown to inhibit cotranslational translocation in vitro (Liu et al, 2009), but the blocked step is unknown. Furthermore a group of closely related cyclic heptadepsipeptide inhibitors including HUN-7293, CAM741 (Besemer et al, 2005) and a simplified version thereof called cotransin (Garrison et al, 2005) have been found to inhibit cotranslational translocation of VCAM1 and other specific substrates (Maifeld et al, 2011;Westendorf et al, 2011). Photoaffinity labeling has identified Sec61a as the target (MacKinnon et al, 2007), which was confirmed by isolation of resistance mutations in SEC61A1 (MacKinnon et al, 2014).…”
Section: Introductionmentioning
confidence: 83%
“…Moreover, these cells are easy to wash because of their epithelial morphology. For the few sensitive proteins reported, the IC 50 values for cotransin-mediated biosynthesis inhibition were in a range of 0.5–5 μM [ 4 , 6 ]. To identify less-sensitive proteins and to discriminate the latter from completely resistant proteins, we used a cotransin concentration of 30 μM for our study which is a saturating concentration taking the reported IC 50 values into account.…”
Section: Resultsmentioning
confidence: 99%
“…Proteins were reduced using dithiothreitol (DTT) (5 mM, 30 min, 55°C) and alkylated using iodoacetamide (15 mM, 30 min, room temperature) in the dark. Separation of the proteins by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) was carried out as described previously [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tag thus seems to be ideally suited to study protein trafficking between different subcellular compartments. Another pc‐FP, namely the Kaede protein, was already used to study real time GPCR recycling [9] and biosynthesis [10]. Kaede seems not to oligomerize when fused to membrane proteins but is prone to tetramerize in its soluble form [9].…”
Section: Discussionmentioning
confidence: 99%